2017
DOI: 10.18632/oncotarget.15605
|View full text |Cite|
|
Sign up to set email alerts
|

BALB/c mice immunized with a combination of virus-like particles incorporating Kaposi sarcoma-associated herpesvirus (KSHV) envelope glycoproteins gpK8.1, gB, and gH/gL induced comparable serum neutralizing antibody activity to UV-inactivated KSHV

Abstract: Infection with Kaposi sarcoma-associated herpesvirus (KSHV) is estimated to account for over 44,000 new cases of Kaposi sarcoma annually, with 84% occurring in Africa, where the virus is endemic. To date, there is no prophylactic vaccine against KSHV. KSHV gpK8.1, gB, and gH/gL glycoproteins, implicated in the virus entry into host cells, are attractive vaccine targets for eliciting potent neutralizing antibodies (nAbs) against virus infection. We incorporated gpK8.1, gB, or gH/gL on the surface of virus-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…However, since the input plasmids transfected into the cells was based on total DNA amount, rather than equal copy number, there is some variation in expression among different glycoproteins. For most of the KSHV glycoproteins, their corresponding bands, as reported by other groups, were detected by immunoblot in the total cell lysates [17,20,22,35]. However, the molecular weight of the gM protein in our study is higher than its theoretical size of 45 kDa.…”
Section: Kshv Envelope Glycoprotein Expression In 293t Cellssupporting
confidence: 52%
See 1 more Smart Citation
“…However, since the input plasmids transfected into the cells was based on total DNA amount, rather than equal copy number, there is some variation in expression among different glycoproteins. For most of the KSHV glycoproteins, their corresponding bands, as reported by other groups, were detected by immunoblot in the total cell lysates [17,20,22,35]. However, the molecular weight of the gM protein in our study is higher than its theoretical size of 45 kDa.…”
Section: Kshv Envelope Glycoprotein Expression In 293t Cellssupporting
confidence: 52%
“…Since KSHV envelope glycoproteins are incorporated into the viral surface and are critical for viral entry into permissive cells, they are the candidate antigens for eliciting nAbs through vaccination. In recent years, several studies have shown that immunizing mice or rabbits with Newcastle disease virus-like particles (VLP) expressing KSHV gpK8.1, gB and gH/gL, either alone or together, can elicit nAbs responses against KSHV [16,17]. However, whether these glycoprotein-targeted responses are consistent with those in KSHV-infected individuals with strong neutralizing responses has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids and mutagenesis of KSHV WT-eGFP genome. To generate plasmid for qPCR standardization, full-length WT K8.1 was individually cloned into the pCAGGS mammalian expression vector as described previously (70). To construct gH/gL Fc-6ϫHis-tagged plasmids for protein production, a single transcript expressing WT gL (gL-WT; aa 1 to 139) and the gH ectodomain (aa 1 to 702) was synthesized by Genewiz (South Plainfield, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed in triplicate. An eight-series of 10-fold dilutions of plasmid pCAGGS-K8.1 (70) was used as a standard for absolute quantification of viral genome copies. The sequences of reverse transcriptase qPCR primer sets for amplification of viral ORF targets are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Purified EBV, purified EBV-LPs, cells, or purified protein were prepared for SDS-PAGE as described [59]. Prepared samples were loaded onto a 4-12% polyacrylamide gel for protein separation using 1×MES SDS running buffer (ThermoFisher Scientific).…”
Section: Sds-page Coomassie Staining and Immunoblottingmentioning
confidence: 99%